THE GAMBARAN TINGKAT PENGETAHUAN PENDERITA HIPERTENSI TERHADAP FAKTOR RESIKO STROKE DAN PENCEGAHANNYA 2020 - Norma Amalia; Yulida S; Ai Rokhayati; Tri Hapsari (Politeknik Kesehatan Kemenkes Bandung, 2020)
Around the world around 972 million people or 26.4% of people suffer from hypertension, this number is likely to increase to 29.2% in 2025. Of 972 million people with hypertension, 333 million are in developed countries and 639 are in developing countries including Indonesia. Complications of hypertension according to the Ministry of Health 2017, as many as 51% of Stroke, 45% of Coronary Heart Disease, and 4% suffer from complications of Kidney Failure and Blindness. One of the factors that can influence the behavior of hypertensive patients is knowledge where the more knowledge a person has of eating the better one's behavior towards certain objects. The research methodology used is the SLR design, where data collection is taken from several research results through the google schoolar website and Garuda portal. Results: the results of the study in the first journal the majority of respondents were well-informed (46.6%), in the second journal the majority of respondents had less knowledge (40%), in the third journal the majority of respondents were knowledgeable (68.6%), and in the fourth journal the majority of respondents knowledgeable enough (55.8%). Conclusion: Based on the four journals obtained, the level of hypertension sufferers' knowledge of stroke risk factors in the four articles discussed, two articles show the results of respondents having good knowledge and two other articles showing the results of respondents having less knowledge. Keywords: Knowledge, Complications, Hypertension.